Determination of antibacterial and cytotoxic activities of cymbopogon nardus (L.) rendle fractions - Chiew, Miaw Fang. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Studies were carried out to investigate the antibacIterial actIvIty of 121, 140-144 and 161 fractions of Cymbopogon nardus (L.) Rendle against Staphylococcus aureus and to determine the cytotoxicity of these fractions. The antibacterial activity test was conducted by using disc diffusion method where S. aureus was cultured in Mueller-Hinton media and plant fractions that had been diluted to different concentration were placed on discs as MIC test. The presence or absence of inhibition zones were used to assess the antibacterial property of the plant fractions. For cytotoxicity study, Vero cells were cultured. After cells were confluence, C. nardus fractions which were diluted to various concentrations were treated to the cells before ELISA assay. The cytotoxicity ofthese three fractions was evaluated based on the viability ofcells. From the study, none of the three plant fractions tested showed antibacterial activities against S. au reus . Hence, further study has to be carried out on other C. nardus fractions to identify the antimicrobial compounds. As for cytotoxic study, the toxicity of fractions could not be detennined because the LC50 were not reached even at the lowest fraction concentration. However, this study indicates that there might be interaction between plant fractions and DMSO. Therefore, further study should be carried out to evaluate the possible interaction between plant fractions and DMSO.